Multi-responsive diarylethene-phenolphthalein hybrids by multiple stimuli. Issue 35 (1st September 2016) - Jin, Piaopiao; Cao, Fei; Luo, Qianfu
Abstract: Photochromic diarylethene derivatives cherishing phenolphthalein moieties were designed and constructed. We present efforts to investigate their versatile performances in multi-responsive properties with multiple stimuli of light, acid/base and temperature/heat. Results show their fluorescence could be on–off switched not only by different lights but also by acid/base. Besides lights and acid/base controllable colour change and fluorescence-changing, altering phase states could also tune their colours via different temperature, which is rare performance for diarylethene derivatives. Especially, the photocylization ratio is as high as 100% for compound2o bearing two phenolphthalein groups. These versatile properties are helpful to the design of pH sensitive photoswitches, fluorescent sensors, and molecular logical gates. Graphical abstract: